1997
DOI: 10.1023/a:1018554715962
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Ultrastructural difractometric and chemical evaluations of calcium partially stabilized zirconium (Ca-PSZ) implants were performed in an in vivo study on animals in order to evaluate its biological behaviour. The chemical-morphological investigations demonstrated the presence of an osteogenetic activity at the bone-biomaterial interface. The new-osteogenesis was preceded by the formation of a loose connective tissue around the implants. This mesenchymal-type tissue without a capsular organization, allowing mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It efficiently supports not only chondrogenic activities [295][296][297] , but also the in-vitro expression of cartilage extracellular matrix proteins by human chondrocytes 294 . It can also serve as a carrier for growth factors 298 . Chitosan has not yet been employed as a matrix in animal or human articular cartilage repair studies, its sole clinical use thus far having been to prevent post-surgical adhesions 299 .…”
Section: Carbohydrate-based Polymersmentioning
confidence: 99%
“…It efficiently supports not only chondrogenic activities [295][296][297] , but also the in-vitro expression of cartilage extracellular matrix proteins by human chondrocytes 294 . It can also serve as a carrier for growth factors 298 . Chitosan has not yet been employed as a matrix in animal or human articular cartilage repair studies, its sole clinical use thus far having been to prevent post-surgical adhesions 299 .…”
Section: Carbohydrate-based Polymersmentioning
confidence: 99%
“…Chemical modification of chitosan may enhance certain bioactive properties and increase its solubility in water, thus aiding in the incorporation of rhBMPs, such as in the case of carboxymethyl chitosan. Mattioli-Belmonte et al (1999) reported the use of N,N-dicarboxymethyl chitosan, with delivery of rhBMP, for enhancing cell proliferation and healing in articular cartilage lesions. Recently, rhBMP-2 was immobilized directly on a guided bone-regenerative membrane surface, made of chitosan nanofibres, that functioned as a bioactive surface to enhance bone-healing (Park et al, 2006).…”
Section: Natural Origin Polymersmentioning
confidence: 99%